Reconstrução da mama pós-quadrantectomia: o uso de miogorduroso segmentar do músculo Latissimus Dorsi em decúbito único - Fortaleza, João Batista (2008)
Nowadays more and more immediate breast reconstructions following post cancer treatment are carried out. In the case of radical mastectomy there are a lot of recognized techniques. In the quadrantectomy, the options of defect repairing range from the primary closing to the utilization of reducing plastic surgery techniques. In the case of tumors of the external quadrants there was no option for the rotation of all the Latíssimo do dorso muscle, which usually exceeds the necessary to repair the volume lost. In the literature there are few works about the post quadrantectomy reconstruction and no one when it deals with external quadrants. Here the technique described originally proposed to make possible the replacement of the volume lost in the quadrantectomies of the external quadrants of small breasts, but it also showed to be useful in cases of medium breasts and in lesions which move towards to the subareolar region. The technique consists in the dissection of the lateral segment of the Latíssimo do dorso muscle by prolonging the incision to withdrawal the lesion, in the same dorsal decubitus, followed by its rotation and modeling in order to repair the defect arising out of a cancer removal. Besides the time reduction of the surgery, in many cases it is not necessary a second surgery. Twenty-one women were submitted to quadrantectomies of external quadrants followed by the reconstruction described here. In order to evaluate the method, to each result a score was attributed to volume, form, symmetry, CAP, scar and surface. The average grade was 7.048, equivalent to grade B which confirms the viability of the method.